ANALYSIS OF SCIENTIFIC LITERACY SKILLS AND LEARNING INTEREST OF FIRST YEAR BIOLOGY STUDENTS IN THE TOPIC OF FUNGI - Priscilya Agatha Sumangge Nainggolan; Salwa Rezeqi; Wasis Wuyung Wisnu Brata (Jurnal Pelita Pendidikan, 2023)
Science literacy has become increasingly important for individuals in carrying out their activities. Science education also strives to enhance students' interest in developing knowledge, skills, and thinking abilities. This research aims to determine the science literacy skills of students in the Low-Level Organism Taxonomy course, particularly in the topic of Fungi, and to assess students' learning interest in the same course. The study was conducted at the Department of Biology, Faculty of Mathematics and Natural Sciences, Medan State University. The population of this study consisted of all students from the 2021 Biology program, totaling 120 individuals. The research sample comprised 31 participants selected through purposive sampling technique. This study employed a descriptive research design. The results revealed that students demonstrated a level of science literacy skills in the Fungi topic categorized as Functional Scientific Literacy, with an average percentage of 67.4%. Additionally, the students exhibited high learning interest in the Fungi topic, with an average percentage of 70.72%.